Database modeling & design logical design Tobey Teorey, Sam Lightstone, Tom Nadeau - Teorey, Toby J. (The Morgan Kaufmann series in data management systems, 2006)
Database systems and database design technology have undergone significant evolution in recent years. The relational data model and relational database systems dominate business applications; in turn, they are extended by other technologies like data warehousing, OLAP, and data mining. How do you model and design your database application in consideration of new technology or new business needs?